2021
DOI: 10.1111/ijn.13011
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue among haemodialysis nurses in public and private hospitals in China

Abstract: Aim This study was conducted to identify and compare the levels of compassion fatigue and job satisfaction among haemodialysis nurses in public and private hospitals in China and explore explanatory factors based on sociodemographic and occupational characteristics. Methods A descriptive study was conducted using a self‐designed demographic questionnaire, the Professional Quality of Life Scale and the Minnesota Satisfaction Questionnaire, with responses from 283 haemodialysis nurses working at six public and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In the study by Karkar et al (2015), 32% of dialysis nurses were found to experience high levels of BO, while 59.8% experienced low levels of emotional BO in a study by Ayraler et al (2011). Similarly, Wang et al (2022) found that hemodialysis nurses had high levels of CF. On the other hand, it may be considered a remarkable finding that contributes to the literature since there is limited study examining the CF levels of dialysis nurses, which in the present study were significantly high compared to those of the oncology nurses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the study by Karkar et al (2015), 32% of dialysis nurses were found to experience high levels of BO, while 59.8% experienced low levels of emotional BO in a study by Ayraler et al (2011). Similarly, Wang et al (2022) found that hemodialysis nurses had high levels of CF. On the other hand, it may be considered a remarkable finding that contributes to the literature since there is limited study examining the CF levels of dialysis nurses, which in the present study were significantly high compared to those of the oncology nurses.…”
Section: Discussionmentioning
confidence: 91%
“…A study that addressed the CF levels of nurses working as liver and kidney transplant coordinators reported moderate levels of CF (Kim, 2003). Wang et al (2022) found that hemodialysis nurses had high levels of CF. Similarly, the literature shows that nurses working in the dialysis unit may experience BO because they are highly exposed to intensive and long-term interaction with patients requiring complex technological care (Hayes & Bonner, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Spain revealed that healthcare workers suffered from moderate to high levels of compassion fatigue and burnout during the COVID-19 crisis (Ruiz-Fernández et al, 2020). Wang et al (2022) also reported high levels of burnout and compassion fatigue. In addition, compassion fatigue scores in this study were higher than the results of some studies conducted with nurses before the pandemic in Turkey (Erkorkmaz et al, 2018;Polat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported a high prevalence of compassion fatigue in nurses during the pandemic (Storm & Chen, 2021;Wang et al, 2022). Therefore, the COVID-19 pandemic caused deleterious effects on frontline nurses' mental health (Aloweni et al, 2022;Murat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, public hospitals (especially high-level public hospitals) have stricter management policies for nurses. Thus, HD unit nurses in public hospitals will be more proactive in improving their professionalism in all aspects, so as to achieve professional title promotion or avoid dismissal (18). Moreover, medical staff in public hospitals have more training opportunities and wider channels to acquire knowledge related to vascular access than those in private hospitals, and thus, they have greater knowledge related to vascular access.…”
Section: Impact Of Hospital Nature On the Knowledge Of Vascular Acces...mentioning
confidence: 99%